Lessons from 30 years of clinical diagnosis and treatment of congenital adrenal hyperplasia in five middle European countries - Kovács, J; Votava, F; Heinze, G; Sólyom, J; Lebl, J; Pribilincová, Z; Frisch, H; Battelino, T; Waldhauser, F; Middle European Workshop on Paediatric Endocrinology-Congenital Adrenal Hyperplasia Study Group (The Journal of clinical endocrinology and metabolism, 2001)
Despite the fact that congenital adrenal hyperplasia (CAH) is one of the most common inborn endocrine disorders, some patients are not identified, or may even die, in an acute salt-losing crisis. In a retrospective study covering the last 30 yr, we examined the time elapsing before diagnosis of CAH patients, in 5 Middle European countries, and the mortality rate in diagnosed patients and their siblings during childhood; we also attempted to estimate how many patients are not diagnosed clinically each year. Basic and follow-up clinical data and the family histories of 484 patients with classical forms of CAH diagnosed between 1969 and 1998 were collected and recorded in 5 Middle European countries. The sex-ratio, time elapsing before diagnosis, and mortality among siblings and patients were calculated, and the number of undiagnosed patients was estimated. We found significantly fewer genetic males (43.0%) than females (57.0%) among 484 classic CAH patients, and the percentage of diagnosed boys did not increase with time; 64.7% of them suffered from the salt-wasting (SW) form, and 35.3% from the simple virilizing (SV) form, of the disease. The diagnosis of CAH was established significantly later in males than in females in both forms [SW: 26 vs. 13 days (median), P < 0.0001; SV: 5.0 vs. 2.8 yr, P = 0.03]. Infant mortality in the general population was significantly lower than in either siblings (1.8% vs. 7.0%; P < 0.0001) or in SW (2.29% vs. 11.3%; P < 0.0001). According to our calculations, by our current praxis of clinical ascertainment, 2-2.5 SW and up to 5 SV stay undiagnosed, out of 40 expected CAH patients per year in the countries investigated. Both clinical detection and treatment of CAH patients, at least in males, were insufficient in the five Middle European countries examined during the last 30 yr. Neonatal mass screening and/or greater awareness of the medical community are discussed as ways of improving the efficacy of CAH management. Our experience may be applicable to other countries with similar health care systems.
Keywords: Female; ženské pohlaví; Slovenia; Time Factors; časové faktory; Slovakia; lidé; Austria; míra přežití; Sex Characteristics; retrospektivní studie; Slovinsko; Male; Czech Republic; pohlavní dimorfismus; Survival Rate; Hungary; Česká republika; kongenitální adrenální hyperplazie; Slovenská republika; mužské pohlaví; Maďarsko; Retrospective Studies; Adrenal Hyperplasia, Congenital; Rakousko; Humans